2017
DOI: 10.1016/j.enpol.2016.12.044
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the cost of saving electricity through U.S. utility customer-funded energy efficiency programs

Abstract: The program administrator and total cost of saved energy allow comparison of the cost of efficiency across utilities, states, and program types, and can identify potential performance improvements. Comparing program administrator cost with the total cost of saved energy can indicate the degree to which programs leverage investment by participants. Based on reported total costs and savings information for U.S. utility efficiency programs from 2009 to 2013, we estimate the savings-weighted average total cost of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…As they would lower supply-side investment requirements, such measures would not need to mobilise higher levels of funding. By mapping the cost of energy efficiency measures under a US utility's efficiency program, Hoffman et al (2017) found the 'savings-weighted average cost' of efficiency measure to be 46 USD/MWh 12 across all sectors. The residential sector cost averaged at 30 USD/ MWh whereas for the non-residential sectors cost savings averaged at 53 USD/MWh.…”
Section: Discussionmentioning
confidence: 99%
“…As they would lower supply-side investment requirements, such measures would not need to mobilise higher levels of funding. By mapping the cost of energy efficiency measures under a US utility's efficiency program, Hoffman et al (2017) found the 'savings-weighted average cost' of efficiency measure to be 46 USD/MWh 12 across all sectors. The residential sector cost averaged at 30 USD/ MWh whereas for the non-residential sectors cost savings averaged at 53 USD/MWh.…”
Section: Discussionmentioning
confidence: 99%
“…EERSs are measured in a variety of ways including spending on efficiency as a percentage of utility revenues, or as an amount per customer, or as savings as a percentage of sales. EERSs both raise electricity prices and provide direct investment in efficiency improvements which reduce monthly bills [135]. Through EERSs, utilities offer customers energy efficiency incentives for efficient products and home performance audits [136].…”
Section: Efficiency Of Electricity Usementioning
confidence: 99%
“…Low-income communities have a high potential for energy savings. More than 30% of households in the United States qualify for low-income energy assistance, but utility spending in that segment comprises only 17% of overall efficiency spending (Hoffman, Leventis, and Goldman 2017). A 2017 report from the Consortium for Energy Efficiency suggests that U.S. electric utility spending on low-income customers might be even less, only 5% of total expenditures (Consortium for Energy Efficiency 2017).…”
Section: Figure 1 Potential For Energy Efficiency By Sectormentioning
confidence: 99%